Analisis Sistem Penyimpanan Arsip Aktif Pada Unit Pengolah Bidang Perizinan Kantor Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Sidoarjo - Mifta, Aisha Rahma; Utami, Dian Arlupi (Universitas Negeri Surabaya, 2023)
Archives are important and must be managed, especially storage, so that their use value and security can be maintained. The purpose of this study is to analyze how the active archive storage procedure and what obstacles occur during the active archive storage process in the licensing field processing unit of the Sidoarjo Regency One-Stop Investment and Integrated Services Office. This type of research is descriptive qualitative, data collection through observation, interviews, and documentation. The results of this study are that the active archive storage procedure in the licensing field of the Sidoarjo Regency DPMPTSP has not been implemented optimally because several steps in the guidelines are not implemented properly, namely not having an index list, the obstacles that occur are the lack of human resources, inadequate infrastructure in terms of conditions, and the absence of an Archive Storage SOP. The suggestions given are that archive officers must make a list / index card to facilitate the structuring and rediscovery of archives if needed at any time, especially since the storage system used is based on the subject / problem of the archive which requires having an index list / card, adding employees who handle archives and training for staff who help, updating infrastructure in accordance with archival standards, and making a new Active Archive Storage SOP tailored to the stages carried out for archive storage in the licensing field.